Atomic structure of Cs grown on Si(001)(2x1) surface by coaxial impact collision ion scattering spectroscopy - Kim, JY; Park, JY; Seo, JH; Whang, CN; Kim, SS; Choi, DS; Kang, HJ; Chae, KH (ELSEVIER SCIENCE BV, 2003)
The atomic structure and the saturation coverage of Cs on the Si(0 0 1)(2 x 1) surface at room temperature have been studied by coaxial impact collision ion scattering spectroscopy (CAICISS). For the atomic structure of saturated Cs/Si(0 0 1)(2 x 1) surface, it is found that Cs atoms occupy a single adsorption site at T3 on the Si(0 0 1) surface. The height of Cs atoms adsorbed at T3 site is 3.18 +/- 0.05 Angstrom from the second layer of Si(0 0 1)(2 x 1) surface. The saturation coverage estimated from the measured CAICISS intensity ratio and the proposed atomic structure is found to be 0.46 +/- 0.06 ML. (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: ENERGY ELECTRON-DIFFRACTION; PHOTOELECTRON DIFFRACTION; COVERAGE; ADSORPTION; CESIUM; 2X1